1001 Cars to Dream of Driving Before You Die - Edited by Heptinstall, Simon and Prefece By Mason, Nick (London Cassell Illustrated, 2012)
It is almost impossible to imagine life today without one of the world- changing inventions of the twentieth century - the car. Appealing to car lovers ranging from vintage car spotters to armchair petrol heads, 1001 Cars You Must Drive Before You Die brings you the world's best cars - Chevrolets from the United States, MGs from Italy, Toyotas from Japan, Porsches from Germany, Aston Martins from the UK and Holdens from Australia. In one of the first truly global guides to cars, they are all here: from Henry Ford's pioneering Model T with its hand-cranked starter to the latest hi-tech vehicles, such as the Lexus LS600h hybrid-powered 4x4 sports saloon.
Include Color Illustration and Glossary
Keywords: Automobiles -- Automobiles -- Pictorial works